The effect of the external medium on the structuralphase transformations of quartzite upon high-energy electron irradiation - Bereznyak, E.P.; Kolodiy, I.V.; Khodyreva, Yu.S. (Вопросы атомной науки и техники, 2019)
The structural transformations of the natural quartzite under the electron irradiation in doses range of 10⁷…10⁸ Gy in various medium were studied using IR-spectroscopy, X-ray diffraction, and crystal-optical analyzes. It was established that under the irradiation, both in air and in a water stream, intense crystallization of the amorphous component occurs, which is siliceous cement. The initial crystal structure of quartzite is also improved as a result of radiation annealing of defects and impurities present in the initial quartz. It was found that the water medium significantly accelerates these processes, however, in the studied doses range for both types of irradiation, degradation of the quartzite crystal structure is not observed. Методами ІЧ-спектроскопії, рентгеноструктурного і кристалооптичного аналізів вивчені перетворення структури природних кварцитів при опроміненні електронами в інтервалі доз 10⁷…10⁸ Гр у різних середовищах. Встановлено, що в результаті опромінення як на повітрі, так і в потоці води відбуваються інтенсивна кристалізація аморфної складової, яка представляє собою кремнеземистий цемент, а також вдосконалення вихідної кристалічної структури кварциту в результаті радіаційного відпалу дефектів і домішок, присутніх у вихідному кварці. Виявлено, що водне середовище істотно прискорює ці процеси, однак у досліджуваному діапазоні доз при обох видах опромінення не спостерігається будь-якої деградації кристалічної структури кварциту. Методами ИК-спектроскопии, рентгеноструктурного и кристаллооптического анализов изучены преобразования структуры природных кварцитов при облучении электронами в интервале доз 10⁷…10⁸ Гр в различных средах. Установлено, что в результате облучения как на воздухе, так и в потоке воды происходят интенсивная кристаллизация аморфной составляющей, которая представляет собой кремнеземистый цемент, а также совершенствование исходной кристаллической структуры кварцита в результате радиационного отжига дефектов и примесей, присутствующих в исходном кварце. Обнаружено, что водная среда существенно ускоряет эти процессы, однако в исследуемом диапазоне доз при обоих видах облучения не наблюдается какой-либо деградации кристаллической структуры кварцита.